PENGARUH SOCIAL MEDIA MARKETING DAN EMAIL MARKETING TERHADAP KEPUTUSAN PEMBELIAN ULANG DENGAN CUSTOMER TRUST SEBAGAI VARIABEL MEDIASI - Muhammad Rezza Aditya Pratama; Mulyana (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2025)
The rapid development of technology and changes in consumer behavior have encouraged retail companies to adopt digital marketing as a primary strategy to retain customers. This study aims to analyze the effect of Social Media Marketing and Email Marketing on repurchase intention at Alfamart, with Customer Trust as a mediating variable. A quantitative approach was used through explanatory research, employing purposive sampling of 150 Alfamart consumers in Semarang City who have shopped both online and offline and actively use social media and email. Data analysis was conducted using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that Social Media Marketing has a positive and significant effect on Customer Trust and Repurchase Intention. Customer Trust also has a positive and significant effect on Repurchase Intention and mediates the relationship between Social Media Marketing and Repurchase Intention. Conversely, Email Marketing has a positive but insignificant effect on Customer Trust and a negative, insignificant effect on Repurchase Intention. The implication of this research is that companies should prioritize interactive and credible social media marketing strategies over email marketing and reassess segmentation and content personalization in email campaigns to enhance their effectiveness.